2014
DOI: 10.1016/j.biocon.2013.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Coffee landscapes as refugia for native woody biodiversity as forest loss continues in southwest Ethiopia

Abstract: ' are cited in the text but not provided in the reference list. Please provide them in the reference list or delete these citations from the text. Q5In the reference list 'Hundera et al. (2013a) and Hundera et al. (2013b)' are mentioned as separate references. Therefore we have changed all citations of Hundera et al. (2013) to Hundera et al. (2013a,b). Please amend the citations in the text if necessary. Q6Please specify the significance of footnotes 'a-c and ⁄' cited in the Tables 1 and 2, as a correspondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 37 publications
5
81
1
Order By: Relevance
“…S1-S4) and local people rely on these church forests for the provisioning of livestock feed, tree seedlings, fuelwood, honey, clean water and other essential ecosystem services including shade, climate regulation, habitat for pollinators and spiritual values (Cardelús et al 2012;Amare et al 2016). In the southwest of the country, shade coffee cultivation has, until now, guaranteed that more or less natural forest remained an important land cover (Tadesse et al 2014), despite the clear trade-off between coffee productivity and forest ecological quality (Senbeta and Denich 2006;Schmitt et al 2010;Aerts et al 2011;Hundera et al 2013). In the central and northern Ethiopian highlands, however, high historical land use pressure has resulted in widespread deforestation and land degradation (Darbyshire et al 2003;Nyssen et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…S1-S4) and local people rely on these church forests for the provisioning of livestock feed, tree seedlings, fuelwood, honey, clean water and other essential ecosystem services including shade, climate regulation, habitat for pollinators and spiritual values (Cardelús et al 2012;Amare et al 2016). In the southwest of the country, shade coffee cultivation has, until now, guaranteed that more or less natural forest remained an important land cover (Tadesse et al 2014), despite the clear trade-off between coffee productivity and forest ecological quality (Senbeta and Denich 2006;Schmitt et al 2010;Aerts et al 2011;Hundera et al 2013). In the central and northern Ethiopian highlands, however, high historical land use pressure has resulted in widespread deforestation and land degradation (Darbyshire et al 2003;Nyssen et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These forests are believed to be the origin and primary center of diversity of Arabica coffee where coffee is still grown in the wild and contains a highly diverse gene pool . However, many of these forests have already been converted to agricultural landscapes, or the remnant forests are managed to produce semi-forest coffee, and a more intensive garden and plantation coffee systems (Table 1; Senbeta & Denich, 2006;Tadesse, Zavaleta, & Shennan, 2014;Wiersum, 2008). The semi-forest and smallholder coffee are cultivated under native forest canopies through planting coffee seedlings and allowing natural regeneration of coffee plants and clearing the understory vegetation Senbeta & Denich, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This could be due the reason that H. abysinicca has a natural ability to withstand and grow under an extreme pressure of human influence. Furthermore, Negash et al (2012) and Tadesse et al (2014) suggested that it may be the result of socio-culture, land use and management intensities, and farmers' perceptions on the specified tree in the area that leads the allowance of trees to grow. Furthermore, Table 2 shows a simple descriptive statistics of number of saplings dead for O. africana at all sub watersheds considered for this study.…”
Section: Resultsmentioning
confidence: 99%